Forordet fra Tidskrift for Philologi og Pædagogik. Første Aargang. 1860. - Berg, C.; Fibiger, O.; Forchhammer, J.; Holm, E.; Lyngby, K.J. (AIGIS, 2024)
Forordet fra Tidskrift for Philologi og Pædagogik. Første Aargang. 1860.